To investigate the influence of sound-absorbing materials on the transmission loss of double-wall panel. (2021) - Gupta, Pavan; Parey, Anand
Abstract: Sound transmission characteristics of panels have been extensively examined which is often quantified by transmission loss. Although acoustic materials are usually applied to passive noise solutions. In the present paper, the influence of sound-absorbing materials on the transmission loss of double-walled panels has been studied theoretically. An analytical method based on statistical energy analysis technique (SEA) is employed for predicting the transmission loss of double-wall steel and aluminum panels. Three commercially available acoustic materials, ie., polyurethane, glass wool, and melamine foam are chosen for investigation.